2011
DOI: 10.1038/leu.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

GSI-I (Z-LLNle-CHO) inhibits γ-secretase and the proteosome to trigger cell death in precursor-B acute lymphoblastic leukemia

Abstract: Gamma secretase inhibitors (GSIs) comprise a growing class of compounds that interfere with the membrane-bound Notch signaling protein and its downstream intra-nuclear transcriptional targets. As GSI-I (Z-LLNle-CHO) is also a derivative of a widely used proteosome inhibitor MG-132, we hypothesized that this compound might be active in precursor-B acute lymphoblastic leukemia (ALL) cell lines and patient samples. We found that GSI-I treatment of precursor-B ALL blasts induced apoptotic cell death within 18–24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 43 publications
3
34
0
2
Order By: Relevance
“…In precursor-B ALL cells, GSI I induces apoptosis by inhibiting Notch signaling and through Notchindependent mechanisms including, besides proteasome inhibition, the increase of reactive oxygen species production and the disruption of the AKT pro-survival pathway. 19 The ability of GSI I to target Notch, AKT and other pro-survival pathways, has also been shown in cutaneous T-cell lymphoma. 50 All these findings have led to an in-depth understanding of the mechanisms of action of GSI I in tumor cells which is essential to define the potential clinical use of GSI I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In precursor-B ALL cells, GSI I induces apoptosis by inhibiting Notch signaling and through Notchindependent mechanisms including, besides proteasome inhibition, the increase of reactive oxygen species production and the disruption of the AKT pro-survival pathway. 19 The ability of GSI I to target Notch, AKT and other pro-survival pathways, has also been shown in cutaneous T-cell lymphoma. 50 All these findings have led to an in-depth understanding of the mechanisms of action of GSI I in tumor cells which is essential to define the potential clinical use of GSI I.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, in these malignancies, minimal clinical responses have been observed, and other studies have also suggested that Notch inhibition is therapeutically effective only when combined with inhibition of other relevant pathogenic pathways. [12][13][14] It has been recently shown that GSI I (Z-Leu-Leu-Nle-CHO), a tripeptide aldehyde inhibiting chymotryptic and aspartyl protease activity, chemically similar to the proteasome inhibitor MG132 (Z-Leu-Leu-Leu-CHO), 15 induces apoptosis in breast 16,17 and glioblastoma tumor cells, 18 and in precursor-B acute lymphoblastic leukemia (ALL) cells 19 by inhibiting both c-secretase and proteasome activity or only proteasome activity. 17 The ability of GSI I to target both Notch and proteasome can render it more effective in inducing antitumor activity in those tumor cells where dysregulated survival and/ or growth are associated with alterations in both Notch signaling and proteasome activity.…”
Section: Chronic Lymphocytic Leukemia (Cll) Is Characterized By Accummentioning
confidence: 99%
See 1 more Smart Citation
“…При предварительной инкубации микс-культуры нейронов и астроцитов с GSI-I в концентрации 100 нМ, что соответствует эффективной концентрации, не вызывающей значительного снижения жизнеспособности клеток [20], к третьим суткам мы обнаружили статистически значимое увеличение экспрессии TS1, TS2 и, в значительно большей степени, чем при действии ингибитора HIF-1 -MMP-9, на фоне уменьшения экспрессии VEGF (рис. 1Б).…”
Section: результаты и обсуждениеunclassified
“…1Б). Однако, с учётом того, что GSI-I способен подавлять убиквитин-протеасомный путь деградации белков [20], стимулирующий эффект этого модулятора на стабилизацию HIF-1 в клетках, находящихся в условиях нормоксии, не может быть исключён. С учётом однонаправленности изменений в экспрессии тромбоспондинов и матриксных металлопротеиназ при применении FM19G11 и GSI-I, логично предположить, что в клетках нейрональной и астроглиальной природы в модели формирующегося ГЭБ в условиях нормоксии FM19G11 может оказывать стимулирующее действие на экспрессию HIF-1 (по аналогии с данными [15]), и к такому же эффекту приводит применение GSI-I, вероятнее всего, за счёт подавления протеасомной деградации HIF-1.…”
Section: результаты и обсуждениеunclassified